Prenatal care during the Covid-19 pandemic: an integrative review (Research, Society and Development, 2022)
Introduction: Prenatal care is essential to identify possible risks in pregnancy, being related to the reduction of maternal-fetal morbidity and mortality. During the Covid-19 pandemic, the challenges for the effectiveness of this service were great, and several strategies were created to increase adherence to pre-delivery care, with telemedicine standing out in this scenario. Objective: To analyze the measures adopted for the maintenance of prenatal care amid the Covid-19 pandemic. Methods: An integrative literature review, carried out in the medical databases PubMed, LILACS and Scielo in July 2022. Results: 30 articles were selected based on the inclusion and exclusion criteria. Discussion: With the Covid-19 pandemic, several strategies for adherence to prenatal care had to be created, such as online communication platforms, apps, formulation of materials to be posted with subjects proposed by patients and people from the community. However, digital methods for counseling were not the only ones used, there were also face-to-face consultations to monitor the pregnancy, but with a reduced number, in which all the necessary equipment was used for adequate social distancing. Conclusion: The Covid-19 pandemic represented a period of limitations and adjustments for prenatal care to remain adequate. For this, the different countries created several to guarantee this access to pregnant women, the main one being telehealth, in which, despite its various restrictions, its benefits for the adequate monitoring of prenatal care are undeniable.